1997
DOI: 10.1046/j.1365-4362.1997.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal antigen tests and the Koebner phenomenon in psoriasis

Abstract: These findings may indicate that intradermal antigens used in this study were more effective in inducing the Koebner phenomenon than injury alone. Furthermore, we observed that there is no meaningful difference between psoriatic and nonpsoriatic subjects in developing cutaneous cellular immune reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…These results were corroborated by the observation that intradermal application of staphylococcal protein A solution produced a more intense erythematous reaction in psoriasis than in atopic dermatitis patients or in healthy controls [11]. Yet, other researchers have reported [12] equivalent cutaneous cellular immune reactions in psoriasis patients when compared to patients suffering from skin diseases other than psoriasis, after intradermal challenge with a series of ‘environmental’ antigens, including PPD. Moreover, even depressed reactivity to PPD has been reported in a small series of patients with guttate psoriasis as compared to healthy controls [13].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…These results were corroborated by the observation that intradermal application of staphylococcal protein A solution produced a more intense erythematous reaction in psoriasis than in atopic dermatitis patients or in healthy controls [11]. Yet, other researchers have reported [12] equivalent cutaneous cellular immune reactions in psoriasis patients when compared to patients suffering from skin diseases other than psoriasis, after intradermal challenge with a series of ‘environmental’ antigens, including PPD. Moreover, even depressed reactivity to PPD has been reported in a small series of patients with guttate psoriasis as compared to healthy controls [13].…”
Section: Introductionmentioning
confidence: 68%
“…Additionally, among the dermatology patients, the psoriasis cohort presents with even larger TST reactions than patients with other skin pathologies leading to hospitalization. Compared to previous corresponding reports in the literature, in this study the number of patients included was notably larger and TST was evaluated per se instead of the ability of intradermal PPD to induce an isomorphic (Köbner) reaction [10, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the cell-mediated reactivify status of psoriasis patients. Tsiouri et al (17) described exacerbated TST responses, while other in vitro and/or in vivo studies found either depressed or normal reactivify (18)(19)(20)(21). The reasons for such discrepancies are unclear, but may be related to differences in severify of the psoriasis, immunosuppressive treatment, and immunological tests employed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, important immunologic mechanisms take place in even apparently healthy skin of psoriatic patients; the proinflammatory state can lead to an overreaction to antigenic triggers [67]. Another factor that may lead to false-positive results is the Koebner phenomenon (development of psoriatic lesions at the site of trauma), reported after intradermal injection of purified protein derivative (PPD) in psoriatic patients [68]. In contrast, psoriatic patients with negative TST results and positive QFT-G results have been reported [6971].…”
Section: Discussionmentioning
confidence: 99%